(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2020)
In realizing fair and integrity elections, in addition to election participants, election organizers, election dispute resolution institutions, supervision support is also urgently needed as a form of community participation. Therefore, needs to be studied whether in the implementation of elections in Indonesia using an independent election oversight body as it is known so far is the Election Supervisory Board or just like other democratic countries that are sufficiently carried out by election participants and community groups or known as election observers? Therefore, this study uses a normative approach with a post-positivism paradigm, that it must be clear who the election supervision is carrying out to provide a sense of certainty and fairness in elections. This study uses normative juridical methods or doctrinal research.